Kesiapterapan NoSQL Pada UMKM di Yogyakarta - M Sulkhanul Umam; Yanning Tri Hapsari (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
Use of the website of its business processes is not a new thing. In its application, the website requires a database as a medium to accommodate all existing data. But in the current technological development needed a database that is able to exchange data very quickly on a large scale. So that MSMEs that implement websites in their business processes can utilize them optimally. This study aims to measure the readiness of using the NoSQL database at MSMEs in Yogyakarta. Measurements were carried out using the Technology Readiness Index (TRI) by distributing questionnaires to owners and programmers of MSME in Yogyakarta. The results indicate that all TRI constructs are interconnected except the construct is optimistic about discomfort. The inconvenience factor is not a limiting factor when MSME plans to implement the NoSQL database.